2016
DOI: 10.18632/oncotarget.12204
|View full text |Cite
|
Sign up to set email alerts
|

Human PDE4D isoform composition is deregulated in primary prostate cancer and indicative for disease progression and development of distant metastases

Abstract: Phosphodiesterase 4D7 was recently shown to be specifically over-expressed in localized prostate cancer, raising the question as to which regulatory mechanisms are involved and whether other isoforms of this gene family (PDE4D) are affected under the same conditions.We investigated PDE4D isoform composition in prostatic tissues using a total of seven independent expression datasets and also included data on DNA methylation, copy number and AR and ERG binding in PDE4D promoters to gain insight into their effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 70 publications
6
29
0
Order By: Relevance
“…In line with the PDE4D isoform expression pattern that we observed in the initial cell line and xenograft studies [65], across the clinical data sets we found evidence for consistent transcription of PDE4D1 and PDE4D2 short forms as well as clear evidence of consistent transcription of PDE4D5, PDE4D7 and PDE4D9 [72,73]. Inconsistent expression patterns were noted for the other long forms of PDE4D [72]. Consequently, we focused our attention on the analysis of the PDE4D1 and PDE4D2 short isoforms and the PDE4D5, PDE4D7 and PDE4D9 long forms.…”
Section: Verification Of the Results Generated During The Discovery Psupporting
confidence: 80%
See 2 more Smart Citations
“…In line with the PDE4D isoform expression pattern that we observed in the initial cell line and xenograft studies [65], across the clinical data sets we found evidence for consistent transcription of PDE4D1 and PDE4D2 short forms as well as clear evidence of consistent transcription of PDE4D5, PDE4D7 and PDE4D9 [72,73]. Inconsistent expression patterns were noted for the other long forms of PDE4D [72]. Consequently, we focused our attention on the analysis of the PDE4D1 and PDE4D2 short isoforms and the PDE4D5, PDE4D7 and PDE4D9 long forms.…”
Section: Verification Of the Results Generated During The Discovery Psupporting
confidence: 80%
“…In particular, we wanted to build on our original cell line and xenograft study [65] and understand which PDE4D isoforms are expressed in prostate cancer tissue and whether there are selective, disease-associated changes in PDE4D isoform expression concerning the known short (PDE4D1, PDE4D2, PDE4D6) forms and the long (PDE4D3, PDE4D4, PDE4D5, PDE4D7, PDE4D8 and PDE4D9) forms and if this might provide a multifactorial signature for PDE4D expression in prostate cancer. In line with the PDE4D isoform expression pattern that we observed in the initial cell line and xenograft studies [65], across the clinical data sets we found evidence for consistent transcription of PDE4D1 and PDE4D2 short forms as well as clear evidence of consistent transcription of PDE4D5, PDE4D7 and PDE4D9 [72,73]. Inconsistent expression patterns were noted for the other long forms of PDE4D [72].…”
Section: Verification Of the Results Generated During The Discovery Psupporting
confidence: 80%
See 1 more Smart Citation
“…It has been demonstrated that PDE4D is aberrantly expressed in patients with prostate cancer and tamoxifen-resistant breast cancer cells (47,48). Although a more systematic approach is required to reach any substantial conclusion, the RT-qPCR data indicated that DLD-1 cells highly express PDE4D.…”
Section: Discussionmentioning
confidence: 99%
“…Phosphodiesterase 4D (PDE4D) is a subtype of metallohydrolases, and was characterized as a tumor-promoting factor in several types of cancers (14). Previous studies reported that high expression of PDE4D promotes cell proliferation and cancer growth in prostate cancer (15)(16)(17). A recent study found that PDE4D was over-expressed in nasopharyngeal carcinoma (NPC) tissues and cells.…”
Section: Discussionmentioning
confidence: 99%